2017
DOI: 10.1371/journal.pone.0170277
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Two Kinds of Iranian Honey and Diphenhydramine on Nocturnal Cough and the Sleep Quality in Coughing Children and Their Parents

Abstract: Coughing in a child induced by upper respiratory tract infections (URTIs) can be a problem, both for the child and its parents. Current studies show a lack of proven efficacy for over-the counter (OTC) medications, but promising data support the use of honey for children. The aim of this study was to compare the effects of two kinds of Iranian honey with diphenhydramine (DPH) on nocturnal pediatric coughs and the sleep quality of children and their parents. This was a clinical trial (registered in IRCT; No.: 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…For millennia, the medicinal properties of honey have been used by mankind. This popular bee product is versatile and is effective against microbes [1][2][3][4], reducing inflammation [5], combating cancer [6], hypertension [7], and liver disease [8], aids in wound healing [3,9] and provides cough relief [10]. An important therapeutic quality of honey is its antimicrobial activity [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…For millennia, the medicinal properties of honey have been used by mankind. This popular bee product is versatile and is effective against microbes [1][2][3][4], reducing inflammation [5], combating cancer [6], hypertension [7], and liver disease [8], aids in wound healing [3,9] and provides cough relief [10]. An important therapeutic quality of honey is its antimicrobial activity [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Nighttime sleep aids containing only antihistamines may also help the body combat the symptoms of the common cold by facilitating sleep, although studies have shown mixed results. A study in which children with infection-induced cough received diphenhydramine at bedtime showed that the extent to which cough had affected children's ability to sleep was significantly decreased compared with baseline [15]. However, another study suggested that diphenhydramine and dextromethorphan were not superior to placebo in terms of improving cough relief in children [16].…”
Section: Discussionmentioning
confidence: 99%
“…1 Other studies had also reported similar results. 11,12,[14][15][16][17][18][19][20][21] In spite of the significant improvement in nocturnal cough severity and frequency among the studied sample, parents and caregivers reported less satisfaction rates (p=0.025), and fewer intentions to re-use it in future attacks (p=0.025). This may be attributed to the fact that using honey, in spite of improving the nocturnal cough frequency and severity scores, did not have a significant impact on the quality of sleep either of children or their parents.…”
Section: Discussionmentioning
confidence: 99%